Amylin and preptin regulate glucose homeostasis in infertile women with polycystic ovary syndrome and poor responders undergoing IVF/ICSI - Celik, N.; Acet, M.; Kenanoglu, O.; Yardim, M.; Acet, T.; Celik, O.; Aydin, S. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY
Keywords: Follicular fluid; amylin; preptin; polycystic ovary syndrome; infertility